Neglected players: Tumor associated neutrophils involvement in chronic lymphocytic leukemia progression - Podaza, Enrique Arturo (2019)
The old paradigm that establishes that neutrophils are just short half-life cells committed to kill bacteria in situ at early stages of infection is changing. Nowadays, there are plenty of reports that focus on neutrophils participation in tumor microenvironment giving rise to the so-called Tumor Associated Neutrophils (TANs)...